Vibration attenuation in wind turbines: A proposed robust pendulum pounding TMD. (15th April 2021) - Chapain, Suvash; Aly, Aly Mousaad
Highlights: Pendulum PTMD can reduce both displacements and accelerations of slender structures under multi-hazard. The designed control system is robust and outperforms TMD under different excitations including earthquakes. Frequency ratio, gap, and pounding stiffness have a significant influence on the control performance. Design charts are developed to enable the selection of optimum parameters for the reduction of desired structural responses. Multiple pendulum PTMDs can be realized in tall buildings with appropriate distribution. Abstract: A pendulum pounding tuned mass damper (PTMD), based on Hertz contact law, is proposed for vibration suppression in wind turbines. A boundary consisting of viscoelastic material is employed to dissipate energy. A wind turbine equipped with the pendulum PTMD is modeled following the Lagrangian method, to facilitate the numerical study. An example of a 5 MW wind turbine from the National Renewable Energy Laboratory (NREL) is studied under both harmonic and variable frequency excitations. Optimum values of the dominant parameters of the pendulum PTMD are attained for a wide range of frequency ratios and pounding stiffness, under a variable frequency sinusoidal excitation. The performance of the device is investigated against several parameters including the coefficient of restitution, mass ratio, and stiffness uncertainty in the primary structure. The optimum frequency ratio of the pendulum PTMD can be far different from the corresponding tuned mass damper (TMD). Design charts are developed to enable the selection of optimal device properties, for the minimization of certain optimization objectives. The results show that the proposed pendulum PTMD has higher performance over the corresponding classical TMD, in terms of robustness and capabilities to reduce maximum accelerations and displacements under earthquakes. Overall, the proposed device outperforms the TMD under multiple hazard loadings, and can enhance the dynamic performance, for resilient and sustainable infrastructure.